Efficiency of Agricultural Production Land Use after the Land Consolidation in Cam Khe District, Phu Tho Provinc - Thi Huong, Hoang; Huong, Nguyen Thi Lan (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
This study was conducted in Cam Khe district, Phu Tho province to evaluate the efficiency of land use for agricultural production after land consolidation. The results show that after the consolidation, the average plot increased from 304m 2 to 1,133 m 2 in size, the number of plots decreased from 5.8 to 1.5 per plot per household, and socio-economic efficiency increased significantly for land users. Most of the interviewees responded that they appreciated the policy on land consolidation and mentioned that thanks to land consolidation, transport infrastructure and irrigation were planned, expanded and upgraded, which greatly facilitated mechanical application, labor reduction, and even the saving of some inputs in the production process. However, the certification of land use rights is time consuming. The number of communes in Cam Khe district implementing land consolidation is small and agricultural production related risks are challenges for some households.